Pengaruh Motivasi Akuntan Terhadap Minat untuk Memperoleh Gelar Chartered Accountant (CA) di Wilayah Yogjakarta - Setyawan, Supanji; iswanaji, Chaidir (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. This research is driven by various phenomena, the dynamics of the rapidly growing accounting profession, and the professionalism of an accountant in a particular state accountant register in the ASEAN Economic Community by 2015. The population in this study is an accountant data register in Yogyakarta province amounted to 65, a sample with purposive sampling method was selected then a sample of 40 accountants with 95% confidence level is taken. The data used in this study is the primary data. The results showed that the variables of quality motivation, and social motivation variables proved to positively affect the interest of accountants to obtain Chartered Accountant (CA). In addition, career motivation variables, and economic motivation variables do not provide evidence of positive impact on the interests of state-owned accountants to obtain Chartered Accountant (CA). The results are expected to serve as a reference for further research as well as useful for the institution concerned to provide information and references to increase the interest of accountants to obtain Chartered Accountant (CA) in relation to motivation. Keywords. Accountant; Chartered Accountant (CA); Motivation.Abstrak. Penelitian ini didorong oleh berbagai fenomena, dinamika profesi akuntansi yang begitu pesat berkembang, dan profesionalisme seorang akuntan dalam register akuntan negara tertentu di ASEAN Economic Community pada tahun 2015. Populasi dalam penelitian ini adalah seorang register data Akuntan di Provinsi Yogyakarta berjumlah 65, sampel dengan metode purposive sampling terpilih kemudian sampel sebanyak 40 akuntan dengan tingkat kepercayaan 95% diambil. Data yang digunakan dalam penelitian ini adalah data primer. Hasil penelitian menunjukkan bahwa variabel motivasi kualitas, dan variabel motivasi sosial terbukti berpengaruh positif terhadap minat akuntan untuk memperoleh Chartered Accountant (CA). Selain itu, variabel motivasi karir, dan variabel motivasi ekonomi tidak memberikan bukti dampak positif terhadap kepentingan akuntan BUMN untuk memperoleh Chartered Accountant (CA). Hasilnya diharapkan bisa dijadikan acuan untuk penelitian lebih lanjut sekaligus bermanfaat bagi institusi yang bersangkutan untuk memberikan informasi dan referensi untuk meningkatkan minat akuntan untuk memperoleh Chartered Accountant (CA) dalam kaitannya dengan motivasi.Kata kunci. Akuntan; Chartered Accountant (CA); Motivasi.